Mule trains to mountain roads: the role of working mules in supporting resilient communities in the Himalayas - Kubasiewicz, Laura M.; Watson, Tamlin; Thapa, Sajana; Nye, Caroline; Chamberlain, Natasha (Frontiers in Veterinary Science, 2024)
Working equids play a central role in mountainous communities, but their work often goes unnoticed by the wider world, with sparse documentation of their role, value, or welfare – a state which often extends to their human counterparts. Communities living in the remote Manaslu Valley, Nepal, face a number of uncertainties, including extreme weather events due to the seasonal monsoon and, more recently, the construction of a new road network. Using semi-structured interviews, questionnaires, and Equine Assessment Research and Scoping (EARS) welfare assessments, we outline the specific role of pack mules in supporting the lives of local people, explain the nuanced links between human experience and mule welfare, and gain insight into how people living in this volatile environment manage uncertainty and risk. Mule work was felt to be the ‘only option’ for a sustainable livelihood for most mule owners although, in some cases, mules had enabled respondents to diversify their income. Mule owners with more husbandry experience did not own mules in more positive behavioural states, which may suggest a lack of generational knowledge and support networks. Short-term ongoing risks, such as the monsoon or unstable tracks, had a larger impact both financially and emotionally than the long-term but distant implications of the road construction. Mule owners must constantly balance the risk of working during the monsoon season, when conditions are treacherous but pay was higher, with losing valuable income but keeping themselves and their mules safe; they do, however, have a more mobile option for employment than non-owners. Mules enable a level of resilience and agility for communities living with constant uncertainty and change, which is only beginning to be recognised formally within the sustainable development sphere. Integration of animal welfare into the SDGs would allow humanitarian aid initiatives to strengthen support networks around working equids, which would greatly benefit the mules and humans alike.